PENERAPAN METODE JIGSAW DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN MOTIVASI SISWA KELAS 9 SMPN 8 CIBITUNG - Laras Prastyani, Kinanti; Fadhilah Purwanderi, Jihan; Herawati Putri, Joenitasya; Raafi, Muhammad; Aini Farida, Nur; Makbul, M (IAIN Bone, 2024)
The problem that is currently becoming a public conversation about student motivation is decreasing, especially in learning Islamic Religious Education. Islamic Education is a lesson that provides material in the form of writing and reading the Qur'an which makes sleepy. If this is allowed, it will produce a young generation that is lazy, less intelligent, and less competent. When students' participation is passive, the teacher will be considered a failure in teaching and inappropriate in choosing learning methods. Motivation is the main benchmark of the success of a learning process. Motivation will be formed if there is an intention within us to make students active in the classroom. Teachers must also find ways to make PAI learning interesting so as to generate student learning motivation. This research uses a collaborative method between qualitative and quantitative, where the data we get is sufficient to answer the puzzle of the object to be studied. The author took the research title as above because he wanted to prove that the cooperative learning model of Jigsaw method developed will make learning more interesting and can increase students' learning motivation wherever they are. This Jigsaw method requires learning motivation for students for active learning and has proven successful in its application.Â Keywords: Islamic Religious Education,Motivation,Jigsaw Method